Are we ready to embrace cannabis as a potential treatment for multiple sclerosis in Pakistan? - Asif, Amna; Ali, Sarah; Ijaz, Namra; Amir, Iman (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Multiple Sclerosis (MS), an autoimmune disease, has seen a significant rise in global prevalence over the past decade. It is characterised by a range of clinical manifestations, including cognitive disabilities, vision problems, balance issues, and chronic fatigue. Conventional MS management includes Baclofen, dantrolene, diazepam, and gabapentin 1, yet a definitive cure for this debilitating disease remains elusive. With recent discoveries surrounding cannabis, new hope has emerged in medical research. A recent study documented the reduction in the severity of symptoms with this drug. Filipino et al. [2] compared the outcomes of cannabis users with those on placebo. An additional 216 more people (95% CI 99 more to 332 more) per 1000 reported the benefits of cannabinoids2. Furthermore, a recent survey found that 47% of patients considered using cannabis, 26% had used it, and 16% were current users.3 Amidst this drug's constant success and effectiveness, it found its way to the top of the available treatment options. Consequently, the legalisation of cannabinoids in numerous high-income countries such as the United States, United Kingdom, and France came about. (UNODC) Additionally, The American Academy of Neurology (AAN) categorised oral cannabis as Level A effective which was reaffirmed by European guidelines on palliative care (EAPC) for MS, highly recommending and advocating for the use of cannabis in the management of pain, spasticity, and fatigue in the patients. Despite the well-documented medical miracles of cannabis, Pakistan remains hesitant to utilise a plant that thrives in the subcontinent. Owing to religious and cultural norms, its repercussions are seen in the shape of misconception regarding the addiction potential of the drug, although contrary to popular belief a recent study places the actual addiction rate at a mere 9%.4 The lack of access to cannabis has led many leading hospitals in Pakistan to prescribe alternative treatments for MS, such as rituximab (3.1%), oral steroids (1.2%), and azathioprine (1.2%). Previously, oral and intravenous steroids were the most commonly used (55.8% and 43.6%, respectively).5 Although Pakistan legalised medicinal cannabis production in 2024, cultural resistance remains strong, leaving many patients in need without access. These circumstances necessitate widespread awareness campaigns led by both the government and the medical community. While the large-scale cannabis sales remain illegal in Pakistan, full legalisation could reduce dependency risks and enable monitored medicinal use. Taxation could curb recreational use, enhance accountability, and contribute to economic growth.